Rediscovery of Calisto israeli Torre, with nomenclatural notes on the larger species of Cuban Calisto (Lepidoptera: Nymphalidae: Satyrinae) - Aguila, Rayner Núñez (Zootaxa, 2009)
Thirty-five years after its original description, Calisto israeli Torre has been rediscovered. The species is redescribed using traditional characters and others little or never used before within this genus such as morphology of labial palpi, legs and shape of male androconial patch. Diagnostic characters include the large triangular patch of white scales on the underside of hindwing anal margin, the shape of androconial patch and the male genitalia having an arched aedeagus with a swollen base. New localities are added to its distribution and notes on its habitat and potential hostplants are given. The possible role of Nipe–Sagua–Baracoa Mountains as a center of evolution for the genus Calisto in Cuba is evaluated. The larger species of Calisto from the mountains of Cuba are compared to the Bahamian Calisto sibylla Bates. The isolation of Calisto species on the islands, their low over–water dispersal capacity, as well as habitat and morphological differences support ranking the Cuban species as distinct from C. sibylla.